Economic Student Scientific Publication Model Exploration Factor Analysis (EFA) Approach - Boy Piter Nizu Kekry; Saraswati Shinta Komang; Helius Yare; Daniel Duwiri (Jurnal Sosial Teknologi, 2021)
Background: Our research reveals factor measures, which are generated to encourage economics students to engage in scientific publication and research processes. Research purposes: Availability of motivational models for scientific publications, as a form of developing economics students in the future. Research methods: Estimation using Exploratory Factor Analysis (EFA) approach, with statistical tools Jeffreys's Amazing Statistics Program (JASP) version 0.16.0.0. Research results: This study shows the accuracy of the model, including the calculated value of McDonald's and Cronbach's > 0.700, for the MSA value of 0.762, and the value of Bartlett's test < .001. For the correlation relationship, it is strengthened by the RMSEA number which is between 0.05-0.08. This study forms a 3 factor model for scientific publications of economics students. Conclusion: This study estimates the factors that can encourage the scientific publication model of economics students. Several factors in this research model are in line with the findings of previous researchers. This study shows that the accuracy of the model includes the McDonald's and Cronbach's > 0.700, for the MSA value of 0.762, and the Bartlett's test value < .001. For the correlation relationship, it is strengthened by the RMSEA number which is between 0.05-0.08. Thus, there are 3 factors in this model, namely the role of lecturers and families, students' basic abilities, and academic achievement goals. We realize that there are several theoretical challenges and measurement models, therefore further research is carried out using statistical test instruments and tools such as AMOS, PLS, and LISREL.